THE BUSINESS DEVELOPMENT ASSISTANCE IN POTATO CHIPS MICRO BUSINESS IN WARNASARI VILLAGE PANGALENGAN DISTRICT REGENCY - Trisa Nur Kania; Latifah Adnani; Sigit Pratama; Fahmi Adnan (LPM Universitas Pasundan, 2022)
The micro potato chip business of Service Partners requires efforts to improve and improve several conditions that are still considered to be obstacles to their business activities. More specifically, the problems found in Partners from this service activity relate to the following matters: 1). There needs to be additions to product variants made from potato, so product development is needed that can increase the variety of products that can be sold by partners. Where this can encourage an increase in the number of products that can be marketed or sold by Partners, 2). Layout in the production room, especially in the area where the cleaning/washing area for potato chips raw material is still in the same area as the bathroom and toilet, 3). It is necessary to facilitate the manufacture of brand designs and printing of brand designs that have been designed to be displayed on product packaging, so that the appearance of the packaging is more attractive and differentiates it from similar products. The implementation of the service is carried out through several forms of activities, namely facilitation, counseling and training, in accordance with the criteria for problems that must be resolved by the activity Implementation Team.